Occupational stress and user satisfaction with primary healthcare in Portugal - Roque, Hugo (2015)
The Portuguese primary healthcare sector has suffered changes due to a reform on the lines of the conceptual framework referred to by some authors as "New Public Management." These changes may be generating higher levels of occupational stress with a negative impact at individual and organizational levels. This study examines the experience of stress in 305 health professionals (physicians, nurses and clinical secretaries) and satisfaction with the services provided by them from 392 users. The population under scrutiny is taken from 10 type A and 10 type B Family Health Units (FHU). The results show that 84.2% of professionals report moderate to high levels of occupational stress with the nurses being those with higher levels. Users reported good levels of satisfaction, especially with the nursing services. There were no differences in stress level between type A and type B FHU, though there were at the level of user satisfaction of type B FHU users who show higher levels of satisfaction. It was seen that dimensions of user satisfaction were affected by stress related to excess work.